School dimension of the health culture in the social discourse of doctors in the Second Republic of Poland - Szczepańska, Beata (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The article presents the problem concerning the participation of the medical profession in the forming of the school health culture were passed in the Second Republic of Poland. A contents of the press, mainly medical,constituted the basis of an analysis. They referred more close to the following periodicals: “Wychowanie Fizyczne” [Physical Education], “Opieka nad Dzieckiem”/“Życie Dziecka”/“Życie Młodych” [Child Care/Child Life/Youth Life], “Zdrowie”/“Zdrowie Publiczne” [Health/ Public Health], “Warszawskie Czasopismo Lekarskie” [Warsaw Medical Magazine], “Archiwum Higieny” [Archive of Hygiene]. The creating culture role in the health of the school was discussed on this base in the following aspects: the hygienic-sanitary state of buildings and school devices, the health of pupils and the health care at the school, participation of doctors in the functioning of the pedagogic school activities. The major issues of this article were to show social connotations of medical discourse on providing school health service, promoting hygiene, sanitation and health education. The significant contribution of medical doctors during interwar period was their role in democratization of Polish educational system through social medicine view.